(untitled) - Griem, Hans R. (Cambridge, UK, 1997)
This monograph presents a comprehensive description of the theoretical foundations and experimental applications of spectroscopic methods in plasma physics research. The first three chapters introduce the classical and quantum theory of radiation, with detailed descriptions of line strengths and high density effects. The next chapter describes theoretical and experimental aspects of spectral line broadening. The following five chapters are concerned with continuous spectra, level kinetics and cross sections, thermodynamic equilibrium relations, radiative energy transfer, and radiative energy losses. The book concludes with three chapters covering the basics of various applications of plasma spectroscopy to density and temperature measurements and to the determination of some other plasma properties. Over one thousand references not only guide the reader to original research covered in the chapters, but also to experimental details and instrumentation. This will be an important text and reference for all those working on plasmas in physics, optics, nuclear engineering, and chemistry, as well as astronomy, astrophysics and space physics.
Keywords: Plasma spectroscopy